Managing potential adverse events during treatment with enfortumab vedotin + pembrolizumab in patients with advanced urothelial cancer - Brower, Blaine; McCoy, Asia; Ahmad, Hiba; Eitman, Cheryl; Bowman, I. Alex; Rembisz, Jennifer; Milowsky, Matthew I. (Frontiers in Oncology, 2024)
Cisplatin-based chemotherapy has been the standard of care for patients with locally advanced or metastatic urothelial cancer (la/mUC). Enfortumab vedotin, an antibodydrug conjugate directed to Nectin-4, and pembrolizumab, an immune checkpoint inhibitor, are two therapies that have individually provided a survival benefit in patients with la/mUC. The combination regimen of enfortumab vedotin plus pembrolizumab was evaluated in EV-302 (KEYNOTE-A39; NCT0422385), a phase 3 study that showed statistically significant and clinically meaningful improvement in overall survival, progression-free survival, and a key secondary endpoint of overall response rate versus chemotherapy. Based on these results and those from the EV-103 (KEYNOTE-869; NCT03288545) Dose Escalation cohort, Cohort A, and Cohort K, enfortumab vedotin plus pembrolizumab was granted approval from the US Food and Drug Administration for the treatment of adults with la/mUC. While guidelines and recommendations for the management of adverse events (AEs) have been developed for immune checkpoint inhibitor monotherapy and enfortumab vedotin monotherapy, additional guidance is needed for managing AEs that occur with enfortumab vedotin plus pembrolizumab. As monotherapies, enfortumab vedotin and pembrolizumab are both associated with some of the AEs observed with the combination, such as skin reactions, pneumonitis, and diarrhea, which may confound the attribution of the AE to a specific agent and thereby complicate clinical management. In this manuscript, we aim to provide recommendations for best practice for patient care and the management of AEs of clinical interest for patients with la/mUC receiving enfortumab vedotin plus pembrolizumab, including skin reactions, peripheral neuropathy, hyperglycemia, and pneumonitis. These recommendations were developed based on published guidelines, expert opinions, and the clinical experience of the authors, which include oncologist, advanced practice provider, nursing, and pharmacy perspectives. In addition, guidance on patient education and communication is provided. With vigilant monitoring, early detection, and prompt intervention of treatment-emergent AEs based on recommended approaches described herein, it is the authors' experience that most AEs can be managed with supportive therapy and dose modification/interruptions, allowing patients to continue treatment.